The Implementation of Al - Azhar Curriculum During Covid 19 in SMP Azhari Islamic School Rasuna South Jakarta - Syarifah Syarifah; Nabila Yasmin Syahira (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
The Curriculum is a tool of plans and arrangements regarding the purpose, content and learning materials. The Implementation of a comprehensive curriculum by school for the achievement of more comprehensive educational objectives. With the COVID 19 virus outbreak that occurred, the Minister of Education and Culture issued a letter on the Implementation of Education decision in the Emergency Period of the Spread of COVID 19 by closing learning activities in schools and implementing online learning. Purpose of study 1) to know the implementation of Al-Azhar curriculum during COVID 19 at SMP Azhari Islamic School Rasuna. 2) to know the inhibitory and supporting factors in the implementation of Al-Azhar curriculum during COVID 19 at AZHARI Islamic School Rasuna Junior High School. The research is descriptive qualitative research. Techniques Data collection using: 1) Passive participation observation techniques by conducting observations on al-Azhar curriculum learning online. 2) Technique interview with al-Azhar curriculum teacher. 3) Documentation Techniques by taking information at SMP Azhari Islamic School Rasuna South Jakarta. Data analysis using Miles and Huberman methods with three stages of research, namely data reduction, data presentation, and conclusion. From the analysis data, the results of the study are 1) The Implementation of Al - Azhar curriculum during COVID 19 by combining Al - Azhar and K13 Curruriculum into one in the process of planning, implementation and evaluation. In accordance with government in 2019 and 2020 learning during COVID 19 By using online media Google Classroom, Google Meet, and Via Videocall Whatssapp. 2) inhibitory factors: unstable network, limitations of teacher personnel and parents in the field of technology, limitations of students' ability in the use of Arabic language that is not maximal with the absence of face-to-face so that learning using Indonesia Language. Supporting factors of distance learning are supported by learning applications, providing material summaries in each subject, giving practice questions and assignments or quizzes. Based on the research that has been described. So I want to give advice that is: For schools and teachers must have innovation, creativity and renewal in the implementation of the Al-Azhar curriculum by improving the field of technology and information.